Ang Pagputok ng bulkang Mayon - Philippine Institute of Volcanology and Seismology (Quezon City PHIVOLCS GDAP-A.V. Unit, 1993)
A videorecording documenting the 1993 eruption of Mayon volcano.
Title from title screen.
Editing, Rene A. Arante; photography, Dindo Javier, Mel Pagtalunan, Rene Arante, Ric Villeza; production assistants, Boy Valencia, Lowie De Guzman, Gina Quiambao, Shiela Insauriga; script, Rene Arante; narration, Melo Acuna; musical scoring, Dindo Javier.
Keywords: Volcanic eruptions; Disaster victims -- Philippines -- Bicol; Mayon Volcano (Albay) -- Eruption, 1993.